Contract clientelism: How infrastructure contracts fund vote-buying - Alisha C. Holland; Will Freeman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Where does the money come from to buy votes? We argue that an important source of funds for vote-buying comes from 'contract clientelism', or the provision of public contracts to private firms in exchange for campaign donations. Using quantitative data on Colombian infrastructure contracts, we demonstrate that municipalities exhibit an 'electoral contracting cycle' in which incumbents assign low-quality contracts while on the campaign trail. Contract manipulations are more common in municipalities with higher reports of clientelist activity. Qualitative evidence from two Colombian cities, Barranquilla and Santa Marta, reinforce that infrastructure contractors provide a critical source of campaign finance and can create subnational political monopolies. The main contribution is to question the classic tension between clientelistic distribution and public goods provision. Politicians need to assign public contracts to secure funds for clientelistic handouts but, in so doing, they often promote low-quality public goods and weaken local states.
Keywords: 330; public contracts; campaign finance; vote-buying; clientelism; infrastructure; Colombia; public goods